Global Rebalancing : Implications for Low-Income Countries - Yang, Yongzheng (Washington, D.C. : International Monetary Fund, 2011)
While global rebalancing will mainly involve structural realignment among major advanced and emerging market economies, it could have significant impact on low-income countries (LICs). Simulations using a global general equilibrium model show that a more balanced global economy would tend to improve the current account balance in LICs with limited impact on domestic output. However, there could be adverse terms of trade effects on some LICs as the prices of manufactured goods rise. On the other hand, such prices increases could provide an impetus to export diversification in many LICs, raising growth in the long run. The output and terms of trade effects would be significantly amplified if structural adjustment is impeded by factor immobility and other rigidities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet